(untitled) (Research, Society and Development, 2020)
A food rich in iron and proteins, beans are one of the most cultivated crops in Brazil and in the world, serving as a food and nutritional security factor with the potential to eradicate hunger and malnutrition. Among the factors that influence productivity, mineral nutrition stands out as one of the most relevant, with potassium playing a fundamental role. The aim of this study was to evaluate the performance of common beans cv. Pérola grown with different doses of potassium, applied in two phenological stages. The experiment was conducted in a randomized block design, in a 5 x 2 factorial scheme, five doses of potassium (0, 0.2; 0.4; 0.6 and 0.8 kg ha-1) in two phenological stages (R7 and R8), with four replications. The evaluations were: plant height, number of pods per plant, number of grains per pod, mass of a thousand grains and productivity. The time of application did not interfere in any of the variables analyzed, as opposed to the potassium doses, which showed significant interaction in productivity. Up to a dose of 0.410 kg ha-1 there was an increase in productivity, reaching its maximum value of 4,145.22 kg ha-1. Conversely, above that dose, productivity decreased. Similar behavior occurs with a weight of a thousand grains, which had a maximum weight of 285.06 g at a dosage of 0.460 kg ha-1.